CULTURAL, MORPHOLOGICAL, PATHOGENIC VARIABILITY AND MYCELIAL COMPATIBILITY AMONG THE ISOLATES OF SCLEROTINIA SCLEROTIORUM (LIB.) DE BARY CAUSE OF SCLEROTINIA ROT - POOJA UPADHYAY; A. K. TIWARI; K. S. BISHT (The Bioscan, 2015)
In the present study all the twelve S. sclerotiorum isolates collected from different hosts showed variations in cultural, morphological and pathogenic characteristics. Among different isolates ,Calendula officinalis and Circium arvense isolates were found significantly fast growing. Maximum number of sclerotia (25 no.) was produced in Ocimum sanctum isolate, while minimum (10 no.) in Cajanus cajan. Largest size of sclerotia (4.8x4.2 mm) was observed in Cicer arietinum, while smallest (3.9x3.2 mm) in B. juncea isolates. B. rapa and Solanum melongena isolates were found most virulent, while Phaseolus vulgaris was least virulent. On the basis of mycelial compat- ibility in dual culture study these isolates were classified in four groups viz. Group I- B. juncea, B. rapa and B. campestris var. toria; Group II- P. vulgaris, Cicer arietinum and C. cajan; Group III- O. sanctum and Tegetes erecta; Group IV- Chrysanthemum coronarium, C. arvense, C. officinalis and S. melongena. The present study could be exploited for the identification of resistant sources against S. sclerotiorum causing stem rot in rapeseed- mustard